1996
DOI: 10.1021/ja960722j
|View full text |Cite
|
Sign up to set email alerts
|

AlliumChemistry:  Microwave Spectroscopic Identification, Mechanism of Formation, Synthesis, and Reactions of (E,Z)-PropanethialS-Oxide, the Lachrymatory Factor of the Onion (Allium cepa)

Abstract: Flow pyrolysis of 2-methyl-2-propyl 1‘-propenyl sulfoxide (9b) affords a 98:2 mixture of (Z)- and (E)-propanethial S-oxide ((Z)- and (E)-5b), both characterized by Fourier transform microwave (FT-MW) spectroscopy. Sulfines (Z)- and (E)-5b are also identified by FT-MW in chopped onion volatiles and by NMR spectroscopy in onion extracts. Similarly, flow pyrolysis of 2-methyl-2-propyl vinyl sulfoxide (9c) affords (Z)- and (E)-isomers of ethanethial S-oxide (5a), identified by FT-MW methods. Pyrolysis in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…3 A sample of 2 was transferred to a steel trap and pressurized to about 20 psi above atmospheric pressure with spark gas (∼80% neon/∼20% helium). The gas output from the trap flowed through a 1 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 A sample of 2 was transferred to a steel trap and pressurized to about 20 psi above atmospheric pressure with spark gas (∼80% neon/∼20% helium). The gas output from the trap flowed through a 1 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…3 Since the microwave spectra of the skew rotatomers of 1a and 1b are observed, other conformers must be higher in energy and are not populated in the cold gas pulses. In addition, there are no resolvable splittings of the observed rotational transitions of 1a and 1b.…”
Section: B 1b (E)-ch 3 Ch 2 Chsomentioning
confidence: 99%
See 1 more Smart Citation
“…Musah et al have reported an enzyme that catalyzes the formation of the sulfine LF, (Z)-phenylmethanethial S-oxide, from the roots of Petiveria alliacea, 11) but the reaction catalyzed by this enzyme differed considerably from that catalyzed by onion LFS. While onion LF is produced through an intra-molecular proton (H þ ) substitution reaction, 12) Petiveria LF is produced by a dehydrogenation reaction. Additionally, a database survey failed to identify any known functional domains exhibiting high sequence homology with onion LFS.…”
mentioning
confidence: 99%
“…Specifically, 1propenesulfenic acid (3) has been shown to be the precursor of (Z)-and (E)-propanethial S-oxides (4), the familiar lachrymatory factor of onions (9). Unsaturated sulfenic acid amides have demonstrated usefulness in synthesis (10)(11)(12).…”
Section: [Traduit Par La Rédaction]mentioning
confidence: 99%